Teacher Professional Development in Integrated STEAM Education: A Study on Its Contribution to the Development of the PCK of Physics Teachers - Iva Martins; Mónica Baptista (MDPI AG, 2024)
Integrated STEM education (iSTEM) has attracted attention due to its potentialities regarding students' learning and intentions to pursue STEM-related careers. However, although increasingly popular, iSTEM remains challenging and elusive, particularly from teachers' perspective. This scenario became even more complex with the inclusion of "A", from the Arts. Considering that the quality of teachers is decisive in the success of integrated STEAM education (iSTEAM), it is essential to provide teachers with opportunities to develop their Pedagogical Content Knowledge (PCK) for iSTEAM. In this work, the aim was to understand the effect of teacher professional development (TPD) within iSTEAM on the development of Physics teachers' PCK related to the topic of "Electrical circuits with associations in series and parallel". This study followed a pre-test/post-test design with a single group, which facilitates the subsequent comparison of participants' reported PCK before and after their involvement in the TPD. The results showed that the TPD had a favorable impact on teachers' PCK. The results of this study also contribute to defining a specific PCK for STEAM (STEAM-PCK).